Analysis of Buying Decision Variables for Subsidized Residence (A Case Study at Housing Banyu Herang Regency Garut) - Alam, Bayu Purnama; Larso, Dwi (Journal of Business and Management, 2016)
Abstract- The main themes of this research on the